Gerakan Literasi Keuangan melalui Media Menabung - Azzahra, Khoirunnisa; Romadhina, Anggun Putri; Handayani, Henni Rahayu (ABDIMAS Iqtishadia, 2023)
The rapid development of digital, such as the proliferation of online shopping sites or applications and the ease of making transactions using electronic money, has an impact on the tendency of teenagers to become impulsive buyers, this shows a low awareness of managing finances for future investments. Therefore, this community service activity is aimed at providing education for Darussalam Al Farhan Foundation youth regarding the importance of building financial literacy to be able to manage finances wisely by cultivating an interest in saving from an early age, by presenting speakers who explore more deeply about how to manage finances wisely through the method of saving and including the importance of preparing for financial conditions in the future. This community service activity is carried out using the socialization method. This activity was welcomed by the chairman of the Darussalam Al Farhan Foundation and during the implementation of the activity the participants looked very enthusiastic and gave a positive response, thus carrying out this activity is expected to be able to form a child's mentality that is smart in using and managing finances wisely and is able to grow children's interest in saving.